Evaluation Of Physical Properties Of Liquid Soap Preparations From Virgin Coconut Oil (VCO) And Coconut Oil (CO) - Natalino Nunu Pote (Strada Journal of Pharmacy, 2019)
Soap is a compound of sodium or potassium and fatty acids from animal oils and vegetable fats which is obtained by the oil hydrolysis process which is then followed by a saponification process under alkaline conditions. Making liquid soap products uses the oil phase, namely virgin coconut oil (VCO) and coconut oil (CO).used as raw material for making surfactants. Surfactants are able to reduce surface tension and interfacial tension by producing foam. The characteristic that influences the quality of liquid soap foam is the fatty acid content. The fatty acid content can affect the physical properties of liquid soap products. The different types of coconut oil used cause the fatty acids contained to be different.Physical properties testing is carried out to find outWhich liquid soap formulation from (VCO) and (CO) formula has the best physical properties.The procedure for making this liquid soap uses the Hot Process method. This method is used because it adapts to the heat- resistant characteristics of coconut oil. The results of the research showed that liquid soap preparations from (VCO) and (CO) were evaluated for their physical properties in terms of organoleptic and stability parameters such as foam height test, pH test, homogeneity test, viscosity test and specific gravity test, which obtained a significant value of <0.05. meaning they both have good physical characteristics. As well as respondents' acceptance of the physical properties of liquid soap preparations from (VCO) and (CO) where the results show that respondents have the same satisfaction regarding the quality of liquid soap.